Cultural memory in Warburg and the limitations of the construction of national memory in Colombia: Regenerationism and the Pre-Columbian past (2013)
Topics associated with memory and history occupy a growing space in cultural theories. This prospective study will explore the potential of the ideas of Aby Warburg inresituating aspects of Pre-Columbian past, particularly regarding its images. Warburg offers an analysis based on anthropological considerations, rather than stylisticones, linking together image and memory, especially through the concept of “survival”. This study shows the limitations of Colombian historical discourse, created by Regenerationism. The analysis focuses on the central image of illustrated newspaper: this is a very elaborate image that summarizesa type of historical thought in which there is no space for a past previous to the arrival of the Spanish. Consequently, we show some models of “survival” of the images of this past, and propose the issue of liberating their potential beyond presence in the museum, the tensions between archive and memory, and the need to rescue “remains” and “fragments” as forms of“survival”.